The Efficacy and Safety of DOACs in Inherited Antithrombin Deficiency: A Cohort Study from a Tertiary Referral Center - Dix, Caroline; Doyle, Andrew J.; Breen, Karen; Hunt, Beverley J. (Thrombosis and Haemostasis, 2024)
Individuals with inherited antithrombin deficiency (IATD) have a high risk of venous thromboembolism (VTE). Most VTEs are managed with direct oral anticoagulants (DOACs), but the utility of DOACs in antithrombin deficiency (ATD) is unreported.Patients with IATD treated with DOAC were identified from our institutions' IATD registry. We assessed patients' characteristics, ATD type, and initial VTE characteristics, thrombosis recurrence and bleeding rates.Thirty-three patients received DOACs for 73 (38.5–111.5) months (median (interquartile range)). Prior to taking DOACs, 12 (36%) patients had VTE recurrence: these occurred after anticoagulation was ceased (4), nonadherence to VKA prior to DOAC use (3), or during heparin use in pregnancy (5). There were no VTE recurrences on standard-dose DOAC, except in a noncompliant patient receiving dabigatran. There was one recurrence with compliant DOAC use—a patient receiving rivaroxaban 10 mg. Six (18%) patients experienced clinically relevant bleeding, which was predominantly menorrhagia (5/6). One major bleeding event, intracranial hemorrhage, occurred in a patient receiving full-dose rivaroxaban who had refractory hypertension (0.5 events/100 patient-years). In this cohort, compliant DOAC users had an overall VTE recurrence rate of 0.5/100 patient-years, whereas with low-dose DOACs the event rate was 3.5/100 patient-years.Standard-dose DOACs appear efficacious and relatively safe in IATD.
Keywords: venous thromboembolism; antithrombin deficiency; anticoagulation; direct oral anticoagulants